2010
DOI: 10.3310/hta14270
|View full text |Cite
|
Sign up to set email alerts
|

Weighting and valuing quality-adjusted life-years using stated preference methods: preliminary results from the Social Value of a QALY Project

Abstract: How to obtain copies of this and other HTA programme reports An electronic version of this title, in Adobe Acrobat format, is available for downloading free of charge for personal use from the HTA website (www.hta.ac.uk). A fully searchable DVD is also available (see below).Printed copies of HTA journal series issues cost £20 each (post and packing free in the UK) to both public and private sector purchasers from our despatch agents.Non-UK purchasers will have to pay a small fee for post and packing. For Europ… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
145
4
5

Year Published

2011
2011
2015
2015

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 128 publications
(155 citation statements)
references
References 59 publications
1
145
4
5
Order By: Relevance
“…Both of these projects were completed in 2008 and concluded that the public probably did want to weight QALYs but how to develop these weights remained uncertain (Dolan et al, 2008;Baker et al, 2010). The second edition of NICE"s guide to the methods of technology appraisal states that: "The Institute considers equity in terms of how the effects of a health technology may deliver differential benefits across the population.…”
Section: Introductionmentioning
confidence: 99%
“…Both of these projects were completed in 2008 and concluded that the public probably did want to weight QALYs but how to develop these weights remained uncertain (Dolan et al, 2008;Baker et al, 2010). The second edition of NICE"s guide to the methods of technology appraisal states that: "The Institute considers equity in terms of how the effects of a health technology may deliver differential benefits across the population.…”
Section: Introductionmentioning
confidence: 99%
“…Whilst other studies have presented quality-of-life using a wide range of levels (Baker et al, 2010a), our piloting work indicated that this may be challenging for respondents to interpret. We therefore included only two levels for the 'quality-of-life without treatment' attribute: 50% and 100%.…”
Section: Attributes and Levelsmentioning
confidence: 86%
“…Los autores que abogan por la perspectiva de la demanda, de acuerdo con el enfoque adoptado en otros ámbitos públicos en los que se utiliza el análisis coste-beneficio para tomar decisiones de inversión 21 , consideran que el umbral debe reflejar el valor de consumo que una sociedad otorga a las ganancias marginales en salud 22,23 . La segunda perspectiva se basa en la idea de que adoptar una nueva tecnología que impone costes adicionales al sistema de salud podría necesitar el desplazamiento de servicios existentes.…”
Section: Dos Perspectivas Y Un Umbralunclassified